1992
DOI: 10.1111/j.1151-2916.1992.tb04445.x
|View full text |Cite
|
Sign up to set email alerts
|

Gas Pressure and Temperature Dependences of Thermal Conductivity of Porous Ceramic Materials: Part 1, Refractories and Ceramics with Porosity below 30%

Abstract: A review of experimental results and theoretical models for thermal conductivities of ceramic materials with porosity less than 30% is given. It is shown that the abnormal nonmonotonic pressure and temperature dependences of thermal conductivity arise from the effects of microcracks and porous grain boundaries, characterizing many industrial refractories, and from the competitive influences of classical and novel mechanisms of heat transfer in composite multiphase materials. The latter mechanisms include segre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0
4

Year Published

2001
2001
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(36 citation statements)
references
References 21 publications
0
32
0
4
Order By: Relevance
“…if the grain volume is used instead of the linear size parameter s. Such simulation has been performed and the matching of the GSDF led to much less accord with the experimental data; namely, the function obtained failed to predict the character of GSDF behavior in the region of small grain sizes. This observation seems [4][5][6][7][8][9][10][11][12][13][14][15][16][17] to support the proposition that the division and conglomeration processes may be considered as essentially one-dimensional ones.…”
Section: Theoretical Grain Size Distributionmentioning
confidence: 75%
See 2 more Smart Citations
“…if the grain volume is used instead of the linear size parameter s. Such simulation has been performed and the matching of the GSDF led to much less accord with the experimental data; namely, the function obtained failed to predict the character of GSDF behavior in the region of small grain sizes. This observation seems [4][5][6][7][8][9][10][11][12][13][14][15][16][17] to support the proposition that the division and conglomeration processes may be considered as essentially one-dimensional ones.…”
Section: Theoretical Grain Size Distributionmentioning
confidence: 75%
“…This is also true for electric resistance of copper and gold nanowires [12,13] and dense ceramic materials [14]. These investigations had demonstrated that the deviations of electric and thermal conductivities from the respective bulk properties are primarily related to electron scattering at grain boundary dislocations.…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“…The applied strain rate was 10 À3 s À1 . Thermal conductivity measurements were performed using a stationary method, 5) where a copper specimen and a reference specimen (Macor) of known thermal conductivity were subjected to the same unidirectional heat flux, which was generated by placing the specimens between a heated and a cooled platens. To minimize the thermal resistance between the two specimens and between the specimens and the platens, the specimens were mechanically polished.…”
Section: Methodsmentioning
confidence: 99%
“…a b 23,24). Como se refleja en la Figura 7, el material de alúmina porosa está formado por una fase sólida no continua, con poros no esféricos y con un cierto grado de percolación, por lo que la conductividad no se ajusta con el modelo simple de Eucken (20).…”
Section: Conclusionesunclassified